EFEKTIVITAS PENGGUNAAN PETA KONSEP TERHADAP HASIL BELAJAR SISWA KELAS VII SMP NEGERI 2 PONRE KECAMATAN PONRE KABUPATEN BONE. - Asmah, Sitti (Lembaga Penelitian dan Pendidikan Mandala, 2021)
Abstrack.This research is an experimental study aimed to determine the effectiveness of the use of the Concept Map Method on the Biology Learning Outcomes of Class VII Students at MTs Bulu-Bulu, Tonra District, Bone Regency. The research design was Posttest–Only Control Design. The population in this study were all seventh grade students of MTs Bulu-Bulu, Tonra District, Bone Regency and the sample consisted of two classes, namely class VII A as the control class and class VIIB as the experimental class. Data collection techniques are tests and documentation. The data analysis technique used is descriptive statistical analysis and inferential analysis. Based on the results of the analysis and discussion of the Effectiveness of the Use of the Concept Map Method on the Learning Outcomes of Class VII Students at MTs Bulu-Bulu, Tonra District, Bone Regency, it can be concluded that the average result of the Biology learning outcomes of students in the experimental class is 82.75 while in the control class is 82.75. 74.76. The results of hypothesis testing by t-test, in the calculation of t-test known 3.00 and ttable 2.023 with db of 39, obtained from 21+20 – 2, at a significant level of 0.05 (5 %), so that t count > t table= 3.00 2.023, it can be concluded that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted